Originally Posted by
harbottle Fro the 1D wave equation where the string is clamped at x=0 and x=L
u(x,0) = 0
the initial velocities are given by u'(x,0) = 2x/L for 0 < x < L/2, u'(x,0) = 2(L-x)/L, L/2 < x < L (derivatives wrt t)
---
So the clamp conditions mean that u(0,t) = 0 = u(L,t).
We could integrate the initial velocities to give something, but I'm not sure how that translates to a solution. I'm also confused because if you integrate the given expressions, you'll get something that depends on t, but if we integrate u'(x,0) we'll get u(x,0), so it doesn't seem to make sense to have a t term..